Strategies for Implementing Anti-Corruption Culture Education In Higher Education To Reduce Corruption In Indonesia - Panggabean, Hetty W.A; Janner Simamora; Ganda A.Simbolon; Sulastry Pakpahan; Juana L. Simbolon (Forum Akademisi dan Dosen Peneliti (FAST), 2025)
Indonesia is ranked 115th in the most corrupt countries based on the Transparency International the Global Coalition Against Corruption report in 2023, scoring 34 out of 180 countries. Decree of the Head of PPSDMK No. HK.02.05 / I / III / 2/06238/2014 concerning the Implementation of Anti-Corruption Education and Culture in the Health Worker Education Environment of the Ministry of Health. The purpose of the study was to determine the learning methods, student perceptions and strategies for anti-corruption education at universities to suppress corruption in Indonesia. The research approach used empirical juridical, namely field research, descriptive specifications and qualitative data. The sample of students of the DIII Midwifery Study Program in North Tapanuli was 113 people (total sampling). The location of the study was the DIII Midwifery Study Program in North Tapanuli, Poltekkes, Ministry of Health, Medan. The results of the study, the most effective method in PBAK with case studies, students have the perception of being Agents of Change and can form anti-corruption characters and most students agree with the strategy to suppress corruption in Indonesia with PBAK in universities.